Local Wisdom and Cultural Traditions in Aceh: Navigating Development through the Philosophy of Amanah and Customary Institutions (Journal of Communication and Multidisciplinary studies, 2026)
Aceh offers a profound philosophical reflection on sustainable development through its local wisdom, which acts as a civilization blueprint that inherently rejects greed. This study explores the role of customary institutions, such as Panglima Laot and Keujruen Blang, in managing natural resources through the lens of the Amanah (trust) philosophy. The research uses a qualitative approach to analyze how traditional practices, like Hukom Adat Laot and Meuseuraya, provide a community-based resource management system that is more effective than rigid bureaucracies. The results indicate that indigenous wisdom in Aceh is not merely a collection of artifacts but a navigation system tested by seasons and disasters, promoting environmental sustainability and social harmony. The study concludes that integrating this spiritual and ecological infrastructure into modern policy is essential for achieving inclusive and high-value development.